As memórias como construtoras da identidade em Ponciá Vicêncio, de Conceição Evaristo - Santos, Roseane Delmiro dos (2017)
The present work intends to show the importance of literature teaching in relation to Afro-Brazilian literature. Therefore, for delimitation of the theme, I first propose a discussion about the concept of literature, seen in two ways: black literature and afro-brazilian literature, based on studies carried out by SANTOS; WIELEWICKI (2005), DUARTE (2008), among other scholars. In this perspective, I talk about the afro-brazilian literature of Minas Gerais writer Conceição Evaristo and her Escrevivência (2012), starting from a biographical analysis of the author, relating it specifically to the romance Ponciá Vicêncio, (2003). Objective to understand how the relationship between memory and identity, from the construction of the life of Ponciá and its relation with Nengua Kainda, an old wise woman from the village where the protagonist lived, through the studies carried out by EVARISTO (2009); DUARTE (2008); BOSI (1987), among others. In this sense of identity inheritance and (re)knowledge of an identity, of the valorization of black and Afrodescendant culture, understand how fundamental is to work literature classes in a stimulus bias, so that the students see the Afro-Brazilian literature as a form of knowing their origins, their culture. In addition to theories and discussions, I present a proposal for classroom intervention, developed from the romance Ponciá Vicêncio (2003) which was carried out in a school in the Santa Rita city, in a high school class of the 3rd year.